Answer:
![\sin(x) = \sum\limit^{\infty}_{n = 0} \frac{1}{\sqrt 2}\frac{(-1)^{n(n+1)/2}}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=%5Csin%28x%29%20%3D%20%5Csum%5Climit%5E%7B%5Cinfty%7D_%7Bn%20%3D%200%7D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%5Cfrac%7B%28-1%29%5E%7Bn%28n%2B1%29%2F2%7D%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
Step-by-step explanation:
Given
![f(x) = \sin x\\](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Csin%20x%5C%5C)
![c = \frac{3\pi}{4}](https://tex.z-dn.net/?f=c%20%3D%20%5Cfrac%7B3%5Cpi%7D%7B4%7D)
Required
Find the Taylor series
The Taylor series of a function is defines as:
![f(x) = f(c) + f'(c)(x -c) + \frac{f"(c)}{2!}(x-c)^2 + \frac{f"'(c)}{3!}(x-c)^3 + ........ + \frac{f*n(c)}{n!}(x-c)^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20f%28c%29%20%2B%20f%27%28c%29%28x%20-c%29%20%2B%20%5Cfrac%7Bf%22%28c%29%7D%7B2%21%7D%28x-c%29%5E2%20%2B%20%5Cfrac%7Bf%22%27%28c%29%7D%7B3%21%7D%28x-c%29%5E3%20%2B%20........%20%2B%20%5Cfrac%7Bf%2An%28c%29%7D%7Bn%21%7D%28x-c%29%5En)
We have:
![c = \frac{3\pi}{4}](https://tex.z-dn.net/?f=c%20%3D%20%5Cfrac%7B3%5Cpi%7D%7B4%7D)
![f(x) = \sin x\\](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Csin%20x%5C%5C)
![f(c) = \sin(c)](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Csin%28c%29)
![f(c) = \sin(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Csin%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
This gives:
![f(c) = \frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
We have:
![f(c) = \sin(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Csin%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
Differentiate
![f'(c) = \cos(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%27%28c%29%20%3D%20%5Ccos%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
This gives:
![f'(c) = -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%27%28c%29%20%3D%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
We have:
![f'(c) = \cos(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%27%28c%29%20%3D%20%5Ccos%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
Differentiate
![f"(c) = -\sin(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%22%28c%29%20%3D%20-%5Csin%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
This gives:
![f"(c) = -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%28c%29%20%3D%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
We have:
![f"(c) = -\sin(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%22%28c%29%20%3D%20-%5Csin%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
Differentiate
![f"'(c) = -\cos(\frac{3\pi}{4})](https://tex.z-dn.net/?f=f%22%27%28c%29%20%3D%20-%5Ccos%28%5Cfrac%7B3%5Cpi%7D%7B4%7D%29)
This gives:
![f"'(c) = - * -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%27%28c%29%20%3D%20-%20%2A%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f"'(c) = \frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%27%28c%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
So, we have:
![f(c) = \frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%28c%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f'(c) = -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%27%28c%29%20%3D%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f"(c) = -\frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%28c%29%20%3D%20-%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f"'(c) = \frac{1}{\sqrt 2}](https://tex.z-dn.net/?f=f%22%27%28c%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D)
![f(x) = f(c) + f'(c)(x -c) + \frac{f"(c)}{2!}(x-c)^2 + \frac{f"'(c)}{3!}(x-c)^3 + ........ + \frac{f*n(c)}{n!}(x-c)^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20f%28c%29%20%2B%20f%27%28c%29%28x%20-c%29%20%2B%20%5Cfrac%7Bf%22%28c%29%7D%7B2%21%7D%28x-c%29%5E2%20%2B%20%5Cfrac%7Bf%22%27%28c%29%7D%7B3%21%7D%28x-c%29%5E3%20%2B%20........%20%2B%20%5Cfrac%7Bf%2An%28c%29%7D%7Bn%21%7D%28x-c%29%5En)
becomes
![f(x) = \frac{1}{\sqrt 2} - \frac{1}{\sqrt 2}(x - \frac{3\pi}{4}) -\frac{1/\sqrt 2}{2!}(x - \frac{3\pi}{4})^2 +\frac{1/\sqrt 2}{3!}(x - \frac{3\pi}{4})^3 + ... +\frac{f^n(c)}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%20-%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%20-%5Cfrac%7B1%2F%5Csqrt%202%7D%7B2%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5E2%20%2B%5Cfrac%7B1%2F%5Csqrt%202%7D%7B3%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5E3%20%2B%20...%20%2B%5Cfrac%7Bf%5En%28c%29%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
Rewrite as:
![f(x) = \frac{1}{\sqrt 2} + \frac{(-1)}{\sqrt 2}(x - \frac{3\pi}{4}) +\frac{(-1)/\sqrt 2}{2!}(x - \frac{3\pi}{4})^2 +\frac{(-1)^2/\sqrt 2}{3!}(x - \frac{3\pi}{4})^3 + ... +\frac{f^n(c)}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%20%2B%20%5Cfrac%7B%28-1%29%7D%7B%5Csqrt%202%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%20%2B%5Cfrac%7B%28-1%29%2F%5Csqrt%202%7D%7B2%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5E2%20%2B%5Cfrac%7B%28-1%29%5E2%2F%5Csqrt%202%7D%7B3%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5E3%20%2B%20...%20%2B%5Cfrac%7Bf%5En%28c%29%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
Generally, the expression becomes
![f(x) = \sum\limit^{\infty}_{n = 0} \frac{1}{\sqrt 2}\frac{(-1)^{n(n+1)/2}}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Csum%5Climit%5E%7B%5Cinfty%7D_%7Bn%20%3D%200%7D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%5Cfrac%7B%28-1%29%5E%7Bn%28n%2B1%29%2F2%7D%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
Hence:
![\sin(x) = \sum\limit^{\infty}_{n = 0} \frac{1}{\sqrt 2}\frac{(-1)^{n(n+1)/2}}{n!}(x - \frac{3\pi}{4})^n](https://tex.z-dn.net/?f=%5Csin%28x%29%20%3D%20%5Csum%5Climit%5E%7B%5Cinfty%7D_%7Bn%20%3D%200%7D%20%5Cfrac%7B1%7D%7B%5Csqrt%202%7D%5Cfrac%7B%28-1%29%5E%7Bn%28n%2B1%29%2F2%7D%7D%7Bn%21%7D%28x%20-%20%5Cfrac%7B3%5Cpi%7D%7B4%7D%29%5En)
Answer:
π
Step-by-step explanation:
the formula is V = πr2h
pie times radius to the second power times hight
Answer:
4.8
Step-by-step explanation:
JK is twice as long as LM, so is 4.8 units long.
"Similar" means the sides of one figure have the same ratio as the corresponding sides of the other figure. We see that AB = 2×CD. JK corresponds to AB, and LM corresponds to CD.
__
We could bother to calculate that sides of JKLM are 1.2 times as long as the corresponding sides of ABCD, but that is not necessary. We only need to find a convenient ratio between the side we want and some other known side. I like a ratio of 2, because it is easy to double a number. We find AB=2CD, so JK=2LM=2×2.4 = 4.8.
Part A:
The circumference of the circle is 197.92.
Explanation:
The formula for circumference of a circle is C=2 πr. If you insert the numbers, it would be C=2 x 3.14 x 31.5. Hence, the answer is 197.92.
Part B:
The area is 3117.25 square cm.
Explanation:
The formula for area of a circle is A= πr ². Inserting the numbers, it is A=3.14 x 31.5 ². Therefore the answer is 3117.25 cm ².